Improving the ability to understand mathematical concepts and achievement of self-determination of elementary school students using realistic mathematics education approach - Samura, Asri Ode; Siagian, Muhammad Daut (Mahesa Research Center, 2023)
This study examines the differences in the increase in the ability to understand mathematical concepts and the achievement of students' self-determination using the RME approach. Quantitative research method by way of the experiment using